2013
DOI: 10.1515/jag-2012-0034
|View full text |Cite
|
Sign up to set email alerts
|

North American height datums and their offsets: The effect of GOCE omission errors and systematic levelling effects

Abstract: One of the main scientific objectives of the Gravity field and steady state Ocean Circulation Explorer (GOCE) gravity field satellite mission is its contribution to the global unification of height systems. In this study, we compute the offsets of three height datums in North America (NAVD88, CGVD28 and Nov07) against a common equipotential surface. NAVD88 and CGVD28 are the official vertical datums for the USA and Canada, respectively. Nov07 is the latest unofficial adjustment of the first-order levelling net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The difference of the MSL at the two coasts is about 60 cm and is explained by the difference in MDT (see, e.g., Hayden et al 2012). Many regional distortions are also found in CGVD28 contributing to approximately a one-meter distortion from west to east (Amjadiparvar et al 2013a). A large northwest-southeast tilt in the US levelling data (Wang et al 2012), the reason for which is still unknown (Marc Véronneau, personal communication), is also quite prominent.…”
Section: Effect Of the Indirect Bias Termmentioning
confidence: 92%
See 2 more Smart Citations
“…The difference of the MSL at the two coasts is about 60 cm and is explained by the difference in MDT (see, e.g., Hayden et al 2012). Many regional distortions are also found in CGVD28 contributing to approximately a one-meter distortion from west to east (Amjadiparvar et al 2013a). A large northwest-southeast tilt in the US levelling data (Wang et al 2012), the reason for which is still unknown (Marc Véronneau, personal communication), is also quite prominent.…”
Section: Effect Of the Indirect Bias Termmentioning
confidence: 92%
“…CGVD28 was constrained to the MSL at five TG stations in the Pacific and Atlantic Oceans and in the St. Lawrence River. A comprehensive review of the levelling-based datums in North America can be found in the work by Amjadiparvar et al (2013a). Although no technical paper on CGVD2013 has been published yet, general information about the new Canadian vertical datum can be found in Lamothe et al (2013) and Véronneau et al (2014a, b).…”
Section: The North American Casementioning
confidence: 99%
See 1 more Smart Citation
“…Corrections for various systematic errors were applied to the levelling measurements in Canada and the USA: refraction, rod calibration, magnetic field and astronomical (tidal) corrections. A stepwise adjustment procedure was applied to reduce the accumulation of systematic errors in the levelling network in Canada [1].…”
Section: Gnss/levelling Geoid Heightsmentioning
confidence: 99%
“…The effect of the deflection of the vertical on the computed geoid height is at the submillimeter [8]; therefore, it can be neglected in equation (1). All these errors affect the quality of the GNSS/levelling geoid heights as an external data set for the evaluation of the GGMs.…”
Section: Introductionmentioning
confidence: 99%